PENINGKATAN KELARUTAN SIMVASTATIN MELALUI PENAMBAHAN BAHAN PENGOMPLEKS SULFANILAMID - Arlan Imran; Prisca Safriani Wicita; Zulfiayu Sapiun (JURNAL KATALISATOR, 2023)
Simvastatin is a drug used to lower cholesterol levels in the blood. The mechanism of action of simvastatin is by inhibiting the enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, which competitively inhibits the cholesterol biosynthesis process in the body. Simvastatin is included in the class II BCS (Biopharmaceutics Classification System) drug, which has low water solubility and high permeability. The low solubility of simvastatin in water will affect its bioavailability in the body, which result in a therapeutic effect that is not achieved. Drug complexation is a method used to determine the solubility of a compound by adding a complexing agent. Complexing materials that are often used in other research are materials that do not have therapeutic activity such as cyclodextrin, but ini this study used complexing material from anti-microbial drug class by utilizing the reaction of glucoronide formation in the glucoronic acid structure of sulfanilamide. This research is a quantitative research with a laboratory experimental trial method which aims to see the effect of adding sulfanilamide complexing agents at various concentrations (25 ppm, 50 ppm, 75 ppm, and 100 ppm) on the solubility level of simvastatin using the acid-base titration method. The dissolved simvastatin concentration values ​​for F1, F2, F3, F4, and F5 were 0.261 ± 0.087, respectively; 0.348 ± 0.151; 0.416 ± 0.195; 0.444 ± 0.163; 0.539 ± 0.118. The results obtained showed that the higher concentration of the sulfanilamide complexing agent added, the greater solubility of simvastatin.